Diagnostic Devices: Microneedle‐Based Transdermal Sensor for On‐Chip Potentiometric Determination of K+ (Adv. Healthcare Mater. 6/2014). Issue 6 (June 2014) - Miller, Philip R.; Xiao, Xiaoyin; Brener, Igal; Burckel, D. Bruce; Narayan, Roger; Polsky, Ronen
<x xml:space="preserve">Abstract</x> A transdermal sensing platform for detection of electrolytes is developed by P. R. Miller, R. Narayan, R. Polsky and colleagues. On page 876, hollow polymer microneedles are integrated with a microfluidic chip for detecting potassium using a solid state ion selective electrode transducer. The device could one day be used as an on body point‐of‐care medical diagnostic device. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>